The effect of processing parameters on particle size in ammonia-induced precipitation of zirconyl chloride under industrially relevant conditions - Carter, Geoffrey; Hart, Robert; Rowles, M; Buckley, Craig; Ogden, Mark (Elsevier, 2009)
The effect of pH of precipitation, starting solution concentration, and agitation levels on the particle size of hydrous zirconia precipitates have been investigated. It was found that all three variables affect the particle size of the hydrous zirconia. The smallest particle size is produced by a 0.81 M starting solution, precipitated at pH 12 with a high agitation level. The pH of precipitation was also found to have a significant impact on the type of hydrous zirconia produced. TGA/DTA, micro combustion and TEM / EDS were used to investigate the difference in the powders produced at pH 3 and 12. This work suggests that powders produced at pH 3 will have a structure similar to Zr[OH]4 whilst those at pH 12 are more likely ZrO[OH]2. XRD and micro-combustion suggest that the powders produced at pH 3 retained ammonium chloride whilst those produced at pH 12 did not. The filtration rates for the pH 3 product were significantly faster than that of the powders made at pH 12 which is significant in the industrial production of these materials.